MRI Manifestations in Isolated Ulnar Collateral Ligament Injury of the Thumb (Gamekeeper's Thumb) : A Systematic Review - Hafid Septian Nugroho; Anas Khoeruluman; Lely Sabariyah; Imam Mustika (The International Journal of Medical Science and Health Research, 2026)
Introduction: Gamekeeper's thumb (acute ulnar collateral ligament injury of the thumb metacarpophalangeal joint) is a common sports-related injury. Accurate diagnosis, particularly differentiating Stener lesions from non-displaced tears, is critical for appropriate management. This systematic review synthesizes MRI manifestations and diagnostic performance for isolated thumb UCL injuries. Methods: A systematic literature screening identified studies involving living patients with isolated thumb UCL injury undergoing MRI evaluation. Data extraction focused on MRI techniques, imaging manifestations (ligament morphology, tear patterns, Stener lesions), diagnostic accuracy metrics, and classification systems. Results: The normal UCL demonstrates uniform hypointensity on all sequences with mean thickness 2.0-2.3 mm. Acute injuries show discontinuity, heterogeneous increased signal on fluid-sensitive sequences, and periligamentous edema. Distal insertion tears account for approximately 90% of ruptures. Partial tears demonstrate thickening (>7 mm) with <50% fiber involvement, while complete tears show full-thickness disruption. Stener lesions exhibit a characteristic "yo-yo on a string" appearance with the retracted ligament superficial to the adductor aponeurosis. Pooled MRI sensitivity for UCL tears is 99% (95% CI 92-100%) and specificity 100% (95% CI 87-100%). For Stener lesions, pooled sensitivity is 93% and specificity 98%. MRI significantly outperforms ultrasound for differentiating displaced from non-displaced tears (specificity 92% vs 72%, p<0.05). Discussion: MRI demonstrates exceptional diagnostic accuracy across the severity spectrum of thumb UCL injuries. The modality's superior soft tissue resolution enables direct visualization of the adductor aponeurosis interposition pathognomonic for Stener lesions. Coronal fluid-sensitive sequences provide optimal ligament visualization, while axial images are essential for assessing aponeurosis relationship. Chronic injuries with predominant scarring pose diagnostic challenges as edema is absent. MRI specificity for confirming UCL tears is significantly higher than clinical examination (100% vs 85%, p=0.04). Conclusion: MRI is a highly accurate, non-invasive imaging modality for thumb UCL injuries with pooled sensitivity and specificity exceeding 90%. It is particularly valuable for Stener lesion identification and surgical planning. Clinical examination with ultrasound serves as an efficient initial diagnostic pathway, with MRI reserved for ambiguous cases requiring definitive characterization.